The Mediating Role of Tax Awareness: Understanding and Sanctions on Taxpayer Compliance - Erwin Indriyanto (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
The primary objective of this research is to examine and assess the impact of tax comprehension and tax penalties on taxpayer adherence to tax payment obligations, with tax awareness serving as an intermediary variable. The study will be conducted at the South Jakarta Madya Tax Office. The data utilized in this study were collected from taxpayers who were registered at the South Jakarta Madya Tax Office and voluntarily participated as respondents. This study employs primary data collection methods through direct field research, utilizing questionnaires administered to respondents. The proposed data analysis methodology encompasses several components: descriptive statistical tests, outer model tests, inner model tests, and hypothesis testing. These analyses will be conducted utilizing the comprehensive model of structural equation modeling (SEM) analysis with smartPLS. The findings indicated that the variables of tax comprehension, tax sanctions, and tax awareness exhibited a favorable and statistically significant impact on taxpayer compliance to some extent. The variables about tax comprehension and tax penalties show a clear and statistically significant effect on tax consciousness. Taxpayer compliance is influenced by two key variables: tax understanding and tax sanctions. These variables have been found to have a favorable and significant impact on compliance levels when mediated by tax awareness.